Selective recovery of dissolved Fe, Al, Cu, and Zn in acid mine drainage based on modeling to predict precipitation pH - Park, Sang-Min; Yoo, Jong-Chan; Ji, Sang-Woo; Yang, Jung-Seok; Baek, Kitae (SPRINGER HEIDELBERG, 2015)
Mining activities have caused serious environmental problems including acid mine drainage (AMD), the dispersion of mine tailings and dust, and extensive mine waste. In particular, AMD contaminates soil and water downstream of mines and generally contains mainly valuable metals such as Cu, Zn, and Ni as well as Fe and Al. In this study, we investigated the selective recovery of Fe, Al, Cu, Zn, and Ni from AMD. First, the speciation of Fe, Al, Cu, Zn, and Ni as a function of the equilibrium solution pH was simulated by Visual MINTEQ. Based on the simulation results, the predicted pHs for the selective precipitation of Fe, Al, Cu, and Zn/Ni were determined. And recovery yield of metals using simulation is over 99 %. Experiments using artificial AMD based on the simulation results confirmed the selective recovery of Fe, Al, Cu, and Zn/Ni, and the recovery yields of Fe/Al/Cu/Zn and Fe/Al/Cu/Ni mixtures using Na2CO3 were 99.6/86.8/71.9/77.0 % and 99.2/85.7/73.3/86.1 %, respectively. After then, the simulation results were applied to an actual AMD for the selective recovery of metals, and the recovery yields of Fe, Al, Cu, and Zn using NaOH were 97.2, 74.9, 66.9, and 89.7 %, respectively. Based on the results, it was concluded that selective recovery of dissolved metals from AMD is possible by adjusting the solution pH using NaOH or Na2CO3 as neutralizing agents.
Keywords: NATURAL-WATERS; ADSORPTION; METALS; HYDROZINCITE; IRON; COPRECIPITATION; NARACAULI; SARDINIA; NICKEL; COPPER